2018
DOI: 10.1002/2017rg000586
|View full text |Cite
|
Sign up to set email alerts
|

The Geodetic Signature of the Earthquake Cycle at Subduction Zones: Model Constraints on the Deep Processes

Abstract: Recent megathrust events in Tohoku (Japan), Maule (Chile), and Sumatra (Indonesia) were well recorded. Much has been learned about the dominant physical processes in megathrust zones: (partial) locking of the plate interface, detailed coseismic slip, relocking, afterslip, viscoelastic mantle relaxation, and interseismic loading. These and older observations show complex spatial and temporal patterns in crustal deformation and displacement, and significant differences among different margins. A key question is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 183 publications
1
80
0
Order By: Relevance
“…Geological information bridging the seismic cycle with a fraction of Myr (e.g., 10 2 to 10 5 yr) may come from systematic investigation of terrace uplift (e.g., SAmerica: Bookhagen et al, 2006;Saillard et al, 2009) and long-term trends in mechanical coupling (e.g., across the Andes: Oncken et al, 2006). Geodynamic modelling (e.g., impact of plateau and fore-arc uplift: Vogt and Gerya, 2014a;Sobolev and Muldashev, 2017;Govers et al, 2018) may test which conditions and rheologies, in the context of steady-statelong-term coupling with recurrent seismicity, trigger detachment instabilities on the 10 5 to 10 6 yr scale.…”
Section: Stability Of Mechanical Coupling Through Timementioning
confidence: 99%
“…Geological information bridging the seismic cycle with a fraction of Myr (e.g., 10 2 to 10 5 yr) may come from systematic investigation of terrace uplift (e.g., SAmerica: Bookhagen et al, 2006;Saillard et al, 2009) and long-term trends in mechanical coupling (e.g., across the Andes: Oncken et al, 2006). Geodynamic modelling (e.g., impact of plateau and fore-arc uplift: Vogt and Gerya, 2014a;Sobolev and Muldashev, 2017;Govers et al, 2018) may test which conditions and rheologies, in the context of steady-statelong-term coupling with recurrent seismicity, trigger detachment instabilities on the 10 5 to 10 6 yr scale.…”
Section: Stability Of Mechanical Coupling Through Timementioning
confidence: 99%
“…Three‐dimensional meshes are generated with Gmsh (Geuzaine & Remacle, ) and convergence tests demonstrate that our results are insensitive to further mesh refinement. We use the finite element modeling platform GTECTON (version 2017.1; Govers & Wortel, ; Govers & Wortel, ; Govers et al, ) compiled with PETSc 3.4.2 (http://www.mcs.anl.gov/petsc) to solve the static mechanical equilibrium equations.…”
Section: Model Setupmentioning
confidence: 99%
“…Threedimensional meshes are generated with Gmsh (Geuzaine & Remacle, 2009) and convergence tests demonstrate that our results are insensitive to further mesh refinement. We use the finite element modeling platform GTECTON (version 2017.1; Govers & Wortel, 1993;Govers & Wortel, 2005;Govers et al, 2018) Two types of boundary conditions are imposed on the plate interface: locked (i.e., zero slip allowed) and unlocked (i.e., free to slide with no resistance). We define locked sections as rectangular areas on the megathrust with one side oriented parallel to strike (the along-strike dimension is the fault length) and the other along dip (the fault width) for straightforward comparison with the solutions of Okada (1992; Figure 2).…”
Section: Model Setupmentioning
confidence: 99%
“…Subduction zone earthquake cycle modeling (Avouac et al, 2015;Govers et al, 2018) provides useful insights into many phenomena that are observed seismologically and geodetically, however are often oversimplified by a planar fault surface. Numerical models allow for the simultaneous monitoring of stresses and kinematics, and therefore serve as a useful tool to investigate potential earthquake precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models allow for the simultaneous monitoring of stresses and kinematics, and therefore serve as a useful tool to investigate potential earthquake precursors. Subduction zone earthquake cycle modeling (Avouac et al, 2015;Govers et al, 2018) provides useful insights into many phenomena that are observed seismologically and geodetically, however are often oversimplified by a planar fault surface. Particle dynamics models, such as the discrete element method (DEM), offer a unique approach, wherein particle assemblages interact according to simplified contact laws, yielding complex kinematic and mechanical behaviors within granular, heterogeneous media.…”
Section: Introductionmentioning
confidence: 99%